Triple swabbing allows sensitive MRSA detection in dermatologic patients of a university tertiary care hospital. (4th December 2012) - Daeschlein, Georg; Bloom, Tina; von, Sebastian; Assadian, Ojan; Wagenvoort, Johann HT; Riebe, Helene; Fochler, Sebastian; Al‐Jebori, Abdulkareem; Karsai, Syrus; Kaisermayer, Ellen; Haase, Hermann; Scholz, Sebastian; et al.
Summary Background To optimize preventive measures to control MRSA, we investigated retrospectively the suitability of a multiple site screening model and the optimal sampling technique to detect MRSA in a university‐based phlebology and skin cancer center in Germany. Patients and Methods During 4.5 years samples of 3 712 inpatients in a dermatologic department were analyzed for MRSA by conventional microbiologic cultures and in parallel by PCR. Samples were taken from nares, wounds and skin lesions. Results MRSA was detected in 60 inpatients (1.6%). 268 of 7 269 (3.7%) samples at admission and during hospital stay were found positive ñ 96 (35.8%) of these were swabs of nares, 59 (22.0%) surveillance swabs, 53 (19.8%) wound swabs and 42 (15.7%) from other dermatologic lesions. Twenty‐five of 60 patients (41.7%) were found positive only in the nares, 10 (16.7%) patients only in wounds and 4 (6.7%) patients only in lesions. 166 (61.9%) of all positive culture samples became positive 24 hours after cultivation, 86 (32.1%) after 48 hours, and 16 (6.0%) after 72 hours. Conclusions Highest sensitivity to detect MRSA can be reached by combining three swabs: nares, wounds and skin lesions (ìtriple‐testî). Culture of screening specimens for 72 hours is recommended.